Pengaruh Rasio Keuangan terhadap Financial Distress Perusahaan Pariwisata yang Terdaftar di BEI - Putri, Yosi Ananda Somanta; Nirawati, Lia (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The emergence of the Covid-19 pandemic in Indonesia has triggered the occurrence of financial distress conditions in the tourism industry. This study aims to examine the impact of several financial ratios, namely Liquidity Ratio, Solvency Ratio, Activity Ratio, and Profitability Ratio, on Financial Distress in tourism companies listed on the Indonesia Stock Exchange. The study was analyzed using logistic regression analysis with IBM SPSS Version 25 software. The population in this study consisted of 46 tourism companies listed on the Indonesia Stock Exchange from 2018 to 2022. The sample was determined using purposive sampling technique, with a total of 17 companies included in the sample. The data used in this study were secondary data, obtained from the financial reports of tourism companies published on the Indonesia Stock Exchange from 2018 to 2022. The results of the research indicate that, simultaneously, Liquidity Ratio, Solvency Ratio, Activity Ratio, and Profitability Ratio have a significant impact on the Financial Distress condition. Liquidity Ratio and Profitability Ratio partially influence the financial distress condition in a positive direction. On the other hand, Solvency Ratio and Activity Ratio do not have a significant partial impact on the financial distress condition in a negative direction. Keywords : Financial Distress, Liquidity Ratio, Leverage Ratio, Efficiency Ratio, Profitability Ratio